bird species diversity in Glumpang Tiga subdistrict, Pidie district - Thrina Junita; Asiah M.D; Abdullah Abdullah; Khairil Khairil; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Research entitled